2005
DOI: 10.1158/0008-5472.can-04-3466
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Radiation Injury: Identification of Risk Factors Associated with Regional Hypersensitivity

Abstract: Effective radiation treatment of thoracic tumors is often limited by radiosensitivity of surrounding tissues. Several experimental studies have suggested variations in radiosensitivity of different pulmonary regions. Mice and rat studies in part contradict each other and urge for a more detailed analysis. This study was designed to obtain a more comprehensive insight in radiation injury development, expression, and its regional heterogeneity in lung. The latter is obviously highly critical for optimization of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(94 citation statements)
references
References 44 publications
6
87
0
1
Order By: Relevance
“…Cardiac irradiation is associated with pulmonary dysfunction (20,21). Additionally, the benefit received by reducing the amount of irradiated lung is enhanced by reducing the dose received by the heart (22).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac irradiation is associated with pulmonary dysfunction (20,21). Additionally, the benefit received by reducing the amount of irradiated lung is enhanced by reducing the dose received by the heart (22).…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory frequency is a well validated marker of radiation induced lung damage in rodents (Van Eerde et al 2001, Novakova-Jiresova et al 2005). In our experiments rats immobilized in a plexiglas jig were placed in a transparent, airtight box.…”
Section: Breathing Rate Assaymentioning
confidence: 99%
“…Travis and colleagues [11 Á13] have in particular contributed to the investigation of the nature of the volume effect in lung and the tolerance doses by their experiments in mouse lung, and they have demonstrated a spatial heterogeneity in the radiosensitivity of the mouse lung. A pronounced variation in radiation sensitivity throughout the lung was demonstrated also in rats by Novakova-Jiresova and colleagues [14]. There may be different explanations for the observed volume effects; a spatial heterogeneity in FSU distribution, a spatial heterogeneity in radiation sensitivity of the individual FSUs, and lastly, a spatial heterogeneity in tissue architecture.…”
mentioning
confidence: 79%
“…However, Khan et al [20] ruled out the possibility that irradiation of parts of the abdomen (inferior to the lung) might be responsible for the out-of-field damage in rat lung. Novakova-Jiresova et al [14] observed higher frequency of lung complications in the apex of rat lung as compared to the lung base using a functional endpoint. However, they failed to identify corresponding variations in histo-pathological damage.…”
Section: Discussionmentioning
confidence: 99%